Electron Transport Characteristics of Wurtzite GaN. (9th September 2013) - Abou El-Ela, F. M.; Mohamed, A. Z.
Abstract : A three-valley Monte Carlo simulation approach was used to investigate electron transport in wurtzite GaN such as the drift velocity, the drift mobility, the average electron energy, energy relaxation time, and momentum relaxation time at high electric fields. The simulation accounted for polar optical phonon, acoustic phonon, piezoelectric, intervalley scattering, and Ridley charged impurity scattering model. For the steady-state transport, the drift velocity against electric field showed a negative differential resistance of a peak value of 2.9 × 10 5 m/s at a critical electric field strength 180 × 10 5 V/m. The electron drift velocity relaxes to the saturation value of 1.5 × 10 5 m/s at very high electric fields. The electron velocities against time over wide range of electric fields are reported.